Influence of the vegetarian and carnivore diets on hemoglobin and hematocrit levels - Yalle-Herencia, Oscar (2020)
The present study establishes the degree of influence of the vegetarian and carnivore diets on the hemoglobin and hematocrit levels of students of human medicine of the Universidad Peruana Unión, Lima, 2018. The goal was to find out if people who follow a vegetarian or carnivore diet are deficient in hematocrit and hemoglobin. Out of the vegetarians, 23 followed different types of vegetarianism. The following ranges were considered: hemoglobin (12 - 16 g/dL) and hematocrit (36 - 48 %). It is concluded that, regarding the diet and hemoglobin/hematocrit levels, most respondents show normal ranges, and people who follow a vegetarian diet do not present highly-deficient hematocrit and hemoglobin levels, and have a better nutritional level than those who follow a carnivore diet.